If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -2 = 20x + 4 Reorder the terms: -2 + 12x = 20x + 4 Reorder the terms: -2 + 12x = 4 + 20x Solving -2 + 12x = 4 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. -2 + 12x + -20x = 4 + 20x + -20x Combine like terms: 12x + -20x = -8x -2 + -8x = 4 + 20x + -20x Combine like terms: 20x + -20x = 0 -2 + -8x = 4 + 0 -2 + -8x = 4 Add '2' to each side of the equation. -2 + 2 + -8x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + -8x = 4 + 2 -8x = 4 + 2 Combine like terms: 4 + 2 = 6 -8x = 6 Divide each side by '-8'. x = -0.75 Simplifying x = -0.75
| 2+7cos(x)=4sin^2(x) | | M^2+6m+11=6 | | 12-4b=-8 | | 2w+2(3w+8)=28 | | 2=72/x | | y=x^3-9*x^2+24*x-18 | | 7p-9=-1+8p | | y-7/3=2 | | -6n+10=4-8n | | 10c=2+8c | | 3(b+3)+4(b+2)+b=89 | | 11=-3+z | | 24x+4=19x+4 | | 3x-(4x+6)=x-9 | | 11=-4.9t^2+120t | | 10x^2+12x-1=4x | | 8-(5/7)x-32 | | 2w+3(w+2)+2(w+5)=44 | | -10+k=10-9k | | -9j+10=10j | | -4a+16+6a=-9a | | (7x+3)(x-5)=-2x(5x+6)+x-19 | | -6-7f=-6f | | X-27=84 | | t-10=10-9t | | 2+7cosx=4sin^2x | | 12x+14=134 | | y+2(y+3)+3(y+1)=45 | | 4p-7.3=16.7 | | 8-2w=-w | | -6n=-6-7n | | 8r+10=9r |